Waste of leaf-cutting ants: disposal, nest structure, and abiotic soil factors around internal waste chambers - Verza, Sandra S. [UNESP]; Diniz, Eduardo A.; Chiarelli, Mara F. [UNESP]; Mussury, Rosilda M.; Bueno, Odair C. [UNESP] (Springer Nature, 2017)
Leaf-cutting ants produce large quantities of waste that harbor bacteria and fungi that are harmful to the colony. To be protected from these pathogens, the workers of Atta species present a sophisticated organization to manage harmful material, which can be deposited outside the nest or in internal chambers. However, little is known about the behavior of Acromyrmex species in handling and disposal of waste. Due to some observations, we assume that the same species of Acromyrmex can deposit waste outside the nest and into internal chambers and raise the following question: what determines the occurrence of internal waste chambers in Acromyrmex? To address this question, we verified whether nest depth influences the waste-chamber occurrence. We also verified the nest structure and the abiotic factors of soil beside each waste-chamber: pH and water content of the soil. For this, eight nests were excavated for Acromyrmex balzani and Acromyrmex rugosus rugosus. We verified that not only can the same leaf-cutting ant species deposit debris both outside and inside the nest but also the same nest can present internal chambers and external waste deposit. The soil beside the waste chamber always presented an acidic pH, while the humidity varied widely. Our results showed that the nest depth was highly correlated with the depth of the waste chamber (p = 0.0003) and probably has some influence on waste disposal. The characteristics of the nest and the role of depth in the choice of waste chamber location are discussed.
Keywords: Acromyrmex; Debris chambers; Garbage disposal; Nest depth; Waste management